The life and death of stars - Lang, Kenneth R. (Cambridge : Cambridge University Press, 2013)
In this well-illustrated text, Kenneth R. Lang explains the life cycle of stars, from the dense molecular clouds that are stellar nurseries to the enigmatic nebulae some stars leave behind in their violent ends. Free of mathematical equations and technical jargon, Lang's lively and accessible text provides physical insights into how stars such as our Sun are born, what fuels them and keeps them bright, how they evolve and the processes by which they eventually die. The book demonstrates the sheer scope and variety of stellar phenomena in the context of the universe as a whole. Boxed focus elements enhance and amplify the discussion for readers looking for more depth. Featuring more than 150 figures, including color plates, The Life and Death of Stars is a modern and up-to-date account of stars written for a broad audience, from armchair astronomers and popular science readers to students and teachers of science.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Stellar dynamics